(untitled) (Fiep Bulletin - online, 2011)
This study has for objective to characterize the reasons that take the seniors to choose the swimming as sporting practice and of improvement of the quality of the seniors’ of the Club of the Worker of SESI/AM life. a questionnaire was applied. The treatment released to the obtained data felt through descriptive analysis (average and frequency) and content analysis. The main results appear that due to the retirement, there is an increase of his/her free time, however this senior doesn’t receive along his/her life, a direcionamento for the use of his/her time of leisure and practice of physical activities. With base in information of the media, of the friends and of the doctors, this senior seeks the practice of a physical activity.